A systematic revision of Aprionyx Barnard, an endemic South African genus of Leptophlebiidae (Ephemeroptera) - Ferreira, Ina Susan (Rhodes University, Faculty of Science, Department of Zoology and Entomology)
Aprionyx Barnard, 1940 is the most speciose genus of Leptophlebiidae in South Africa and endemic to the southern region. Like the other African Leptophlebiidae, Aprionyx has received limited research. The earliest described Aprionyx species were based only on adults that were then placed in Atalophlebia Eaton, 1881. The first descriptions of nymphs were contributed by Barnard (1932), with the smooth claws of the nymphs being the distinctive feature that allowed him to create Aprionyx for all of the South African species placed in Atalophlebia at that time. This research aimed to improve knowledge of Aprionyx species by revising its molecular and morphological systematics. Molecular phylogenetic analysis of the COI, 16S and 28S genes generated a species tree illustrating the species' relationships within Aprionyx. Species delimitation analyses (bPTP and GMYC methods) were generally congruent with the molecular phylogenetic species composition. The phylogeny identified up to ten potentially new species, a substantial increase in the species diversity of Aprionyx. Review of the descriptions of the eight named Aprionyx species resulted in major nomenclatural changes concerning A. tabularis (Eaton, 1884), A. phoeocera (Lestage, 1924) stat. rev. and A. intermedius Barnard, 1932 n. syn. With the redescriptions of all currently known species, the nymph of A. rubicundus Barnard, 1932 was described for the first time. An identification key to the species of Aprionyx was compiled from newly recognized descriptive characteristics and, for the first time, includes both imagos and nymphs. Molecular and morphological phylogenetic analyses recovered Aprionyx as monophyletic, although this was poorly supported morphologically. The phylogenies were topologically congruent and identified two clear geographically separated clades, a western and eastern Aprionyx group. Molecularly, morphologically and geographically, these two clades were recovered as two clearly distinct groups within the genus. The analyses further identified three lineages in Aprionyx: rubicundus, pellucidulus and eastern Aprionyx. The estimated age of Aprionyx indicated that initial diversification occurred during the Cretaceous (approximately 100 ma). Aprionyx peterseni (Lestage, 1924) was shown as the oldest of the analysed species, and the main drivers to species diversification were possibly the glacial cycles of the Quaternary period, through the mechanism of river anastomosis during fluctuating sea levels. Further research is needed to strengthen the support for the hypothesis identified in this study, but a substantial foundation has been laid by this work for future research, conservation and environmental decision-making.
Keywords: Biogeography; Leptophlebiidae -- Geographical distribution; Leptophlebiidae -- Morphology; Leptophlebiidae -- Phylogeny; Leptophlebiidae -- Classification